Karakteristik Hukum Islam dan Asas Penerapannya - A Saiful Aziz (Jurnal Iqtisad, 2019)
Abstract Islamic Shari'ah is qadim, meaning that it has existed since before humans (society) existed, because it is the word of God or the words of Allah that is nafs azli which is not literate and has no sound. Because the law was made for humans, Allah revealed something that corrects this thinking in the proposal of fiqhi known as the proposition. These legal propositions are qath'iy and some are resistant to zhanniy. Therefore, Islamic law which is determined directly and affirmed by Allah, means that the laws are derived from the proposition that Qath'iy. The law that stipulates this is not much, and the law that leads to its development is known as sharia, the second law which is determined only by the points intended by the law established by the zhanni proposition. This law is clearly developed very much and can be developed with the term ijtihad.